Experimental evaluation of piecewise exact solution for predicting seismic responses of spherical sliding type isolated structures. - Tsai, C.S (Earthquake engineering & structural dynamics.)
The use of base isolation for enhancing seismic resistibility has been proven as an efficient method in experimental and theoretical studies. It is usual to insert a flexible device in the horizontal direction to permit the most of relative deformation of a structure at this level. Because the rigidity of the superstructure is much higher than that of the base isolator underneath the structure, the behavior of the superstructure can be idealized as a rigid body during earthquakes. In general, hundreds of degrees of freedom and a step by step time history analysis are the basic requirements for calculating the seismic response of a base isolated structure under earthquakes. In order to develop a simple tool which can be easily adopted for calculating the seismic responses of the spherical sliding type isolated structures, a piecewise exact solution for predicting the seismic responses of base isolated structures has been derived in this study. The comparison between the experimental results conducted at the National Center for Research on Earthquake Engineering (NCREE) in Taiwan and the analytical results obtained from the piecewise exact solution show that the formulation derived in this study can predict the seismic responses of the base isolated structure with a very high accuracy.